2012
DOI: 10.3201/eid1804.111267
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Highlands of Ecuador since 1900

Abstract: Eliminated after 1950, malaria may be reemerging in a new region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Machala has a long history of operational mosquito control and surveillance due to high dengue incidence relative to surrounding areas, making it an ideal setting to study delivery systems of vector control services. Formerly, fumigation and control services were deployed from decentralized medical subcenters located throughout Machala as a part of the National Service for the Control of Vector-borne Diseases (in Spanish: Servicio Nacional de Control de Enfermedades Transmitidas por Vectores Artrópodos-SNEM), a vertically structured vector-borne disease eradication program in the Ministry of Health (MoH) [24]. In 2015, SNEM was disbanded and public health surveillance and mosquito control in Machala became decentralized and administered by the local MoH health districts, with two centrally located hubs from which abatement services are deployed ( Fig.…”
Section: Vector Control and Mosquito-borne Diseases In Ecuadormentioning
confidence: 99%
“…Machala has a long history of operational mosquito control and surveillance due to high dengue incidence relative to surrounding areas, making it an ideal setting to study delivery systems of vector control services. Formerly, fumigation and control services were deployed from decentralized medical subcenters located throughout Machala as a part of the National Service for the Control of Vector-borne Diseases (in Spanish: Servicio Nacional de Control de Enfermedades Transmitidas por Vectores Artrópodos-SNEM), a vertically structured vector-borne disease eradication program in the Ministry of Health (MoH) [24]. In 2015, SNEM was disbanded and public health surveillance and mosquito control in Machala became decentralized and administered by the local MoH health districts, with two centrally located hubs from which abatement services are deployed ( Fig.…”
Section: Vector Control and Mosquito-borne Diseases In Ecuadormentioning
confidence: 99%
“…Jatinangor area is a highland area which the lowest point is 675 meter and the highest point is 1281 meter above the sea level. The previous study from Pinault and Hunter 13 showed that Anopheles spp. found in a highland area.…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this preprint this version posted October 18, 2019. ; https://doi.org/10.1101/19009498 doi: medRxiv preprint Enfermedades Transmitidas por Vectores Artrópodos -SNEM), a vertically structured vectorborne disease eradication program in the Ministry of Health (MoH) [24]. In 2015, SNEM was disbanded and public health surveillance and mosquito control in Machala became decentralized and administered by the local MoH health districts, with two centrally located hubs from which abatement services are deployed (Fig.…”
Section: (Which Wasmentioning
confidence: 99%